Modified copper catalysts in methanol oxidation; Proceedings on the XIX Iberoamerican Symposium on Catalysis, Merida, Mexico, 2004 - Pestryakov A. N. Aleksey Nikolaevich; Petranovskii V.; Temkin O.; Belousova V. (2004, 2004)
Features of the process of methanol partial and deep oxidation on supported copper catalysts as compared with silver samples have been studied. The influence of supports of different acid-base nature and modifying additives of Zr, Ce, La and Cs oxides on electronic states of supported copper was investigated by the methods of diffuse reflectance electron spectroscopy, XRD and electron microscopy. By comparison of catalytic and spectroscopic data a conclusion on the nature of active sites of copper catalysts in this process has been made.